2023
DOI: 10.1039/d2gc04682b
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in enzyme/metal–organic framework composites for CO2transformation reactions

Abstract: Enzymatic reactions offer a sustainable alternative to chemical catalysis (chemical, photochemical, and electrochemical) in converting CO2 into value-added product. However, the structural fragility, inadequate stability, and poor recyclability of enzymes...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 187 publications
0
4
0
Order By: Relevance
“…Recently, metal–organic frameworks (MOFs) have been widely used as protective shells for enzymes. Research has shown that MOF shells can enhance their biochemical properties such as thermal stability, reusability, organic solvent resistance, and the stability of encapsulated enzymes through structural constraints. , In addition, the strong interaction between metal ions and imidazole esters enables ZIF-8 to maintain structural integrity in common solvents, including water . Moreover, the synthetic conditions of MOF immobilized enzymes are “green”, without heating, pressure, or organic solvents, which has a positive impact on green chemistry. However, MOFs are crystalline powders with practical limitations such as easy aggregation and recycling difficulties. In addition, they can only be used in stirred reactions and not in continuous fluid catalytic reactions, resulting in low reaction efficiencies. , Therefore, the application of enzyme immobilization in continuous microfluidic reactors has aroused great interest.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, metal–organic frameworks (MOFs) have been widely used as protective shells for enzymes. Research has shown that MOF shells can enhance their biochemical properties such as thermal stability, reusability, organic solvent resistance, and the stability of encapsulated enzymes through structural constraints. , In addition, the strong interaction between metal ions and imidazole esters enables ZIF-8 to maintain structural integrity in common solvents, including water . Moreover, the synthetic conditions of MOF immobilized enzymes are “green”, without heating, pressure, or organic solvents, which has a positive impact on green chemistry. However, MOFs are crystalline powders with practical limitations such as easy aggregation and recycling difficulties. In addition, they can only be used in stirred reactions and not in continuous fluid catalytic reactions, resulting in low reaction efficiencies. , Therefore, the application of enzyme immobilization in continuous microfluidic reactors has aroused great interest.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they can only be used in stirred reactions and not in continuous fluid catalytic reactions, resulting in low reaction efficiencies. , Therefore, the application of enzyme immobilization in continuous microfluidic reactors has aroused great interest. For example, wall-coated reactors and packed-bed reactors that can achieve continuous production and long-term reuse have been successfully developed, but they still have some limitations: low amount of fixed catalyst, high cost, cumbersome packaging operations, and low mass transfer efficiency. Using monolithic materials may be a good choice.…”
Section: Introductionmentioning
confidence: 99%
“…The conversion of CO 2 into high value-added chemicals provides a promising approach to addressing this problem. [1][2][3] Particularly, the cycloaddition of CO 2 with epoxides to synthesize cyclic carbonates has attracted much attention because of the 100% atomic utilization and wide availability of the products in aprotic solvents, battery electrolytes, and pharmaceutical intermediates. [4][5][6][7] Due to the high energy barrier of the ringopening of epoxides (the rate-determining step), 8,9 CO 2 cycloaddition usually requires harsh and energy-intensive conditions such as high reaction temperature, high CO 2 pressure, and cocatalyst/metal/solvent consumption.…”
Section: Introductionmentioning
confidence: 99%
“…As a novel class of crystalline porous materials assembled by metal ions/clusters and functionalized organic ligands, metal–organic frameworks (MOFs) have been widely exploited for various applications such as gas storage and separation, proton conduction, photocatalysis, nonlinear optics, solid-state lighting, optical waveguides, and so on. In terms of optical function MOFs, their inherent long-range periodic order enables the precise arrangement of photoactive chromophore linkers at the molecular level . Meanwhile, the structural diversity of MOFs can highly affect the conformation and spatial stacking mode of the photoactive linkers and then modulate the intermolecular interactions and optical performance. …”
mentioning
confidence: 99%